Welcome to Toronto. Welcome to the CIHR - Malcolm King (Canadian Respiratory Journal)
May 6 to 10, 2000 is a great time for the Canadian respiratory community. It is the 100th anniversary of our Lung Association, and it is our chance to host the respiratory world at the American Lung Association, American Thoracic Society International Conference and the Canadian Thoracic Society Annual Meeting. The name Toronto comes from a Mohawk word meaning 'meeting place'. The rivers that run into Lake Ontario were traditional gathering places for the aboriginal peoples that lived in this area before the coming of the European settlers. My ancestors include both Mohawks and the Mississaugas of the Credit, the native tribe that occupied the Toronto area as its traditional territory until the late 18th century.